IMPLEMENTASI MAHASISWA KAMPUS MENGAJAR 2 DALAM MENINGKATKAN KETERAMPILAN LITERASI DI SEKOLAH DASAR - Iis Irma Lisnawati; J. Julia; Prana Dwija Iswara (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
The Indonesian government's attempt to improve the literacy skills of elementary school students is to implement the MBKM (Merdeka Belajar Kampus Merdeka) program for teaching campuses. Hence, the research described in this article is to investigate the information about the implementation of the Teaching Campus Students 2 program to improve elementary school students’ literacy skills. In addition, the research also involved the barriers, strategies, and evaluation results regarding student literacy. The research used a qualitative research method with a case study design through semi-structured interviews to find out the students' barriers, strategies, and evaluation results. The participants involved 20 students in the Teaching Campus program who were based in elementary schools and spread over the West Java provinces. The data used in the research was a qualitative analysis, which consisted of three activity lines, they are the stages of data reduction, data presentation, and conclusion or verification. The results indicate that the improvement of students' literacy skills was increased enough. It can be seen from the increased students’ interest in reading, the skill to process information, how to find out problems, and students’ skills to provide solutions to the problem. Various innovative learning strategies were successfully designed by Teaching Campus Students 2 and made it one of the factors that made students' literacy skills increase well enough.